Caregiver burden after stroke: changes over time?. Issue 3 (30th January 2020) - Pont, Winke; Groeneveld, Iris; Arwert, Henk; Meesters, Jorit; Mishre, Radha Rambaran; Vliet Vlieland, Thea; Goossens, Paulien; ,
Abstract: Introduction and aim: Many caregivers of stroke patients experience a high burden. This study aims to describe the course of burden in individual caregivers in the first year after stroke. Methods: This study is part of the Stroke Cohort Outcomes of REhabilitation study, a multicentre, longitudinal cohort study including consecutive stroke patients admitted to two rehabilitation facilities. Caregivers were asked to complete the Caregiver Strain Index and questions on their sociodemographic characteristics 6 and 12 months post admission. Patients' sociodemographic and clinical characteristics were extracted from medical records. Results: A total of 129 caregivers were included, 72 completed the Caregiver Strain Index twice. Of them, 19 (26.4%) were men, median age 59 (range 27–78) years. A consistently high or low burden was reported by 15 (20.8%) and 49 (68.1%), respectively, whereas 8 (11.1%) reported a high burden at either 6 ( n = 3) or 12 months ( n = 5). Discussion: In the majority of caregivers of stroke patients the perceived caregiver burden is consistent over time. However, as in 11.1% caregiver burden changes from 6 to 12 months, caregiver burden should be measured repeatedly until 12 months after stroke. Caregivers living together with a patient who suffered a haemorrhagic stroke seem to be more at risk for a high burden. Implications for rehabilitation: Many caregivers of stroke patients experience a high burden. The Caregiver Strain Index score at 6 months is a good predictor for the score at 12 months. In some caregivers the high burden is not yet present at 6 months, therefore monitoring caregiver burden throughout the first year after stroke seems warranted. Caregivers living together with a patient who suffered a haemorrhagic stroke seem to be more at risk for a high burden.